Unusual cause for pacemaker threshold elevation - Yontar, Osman Can; Tenekecioglu, Erhan; Karaagac, Kemal; Tutuncu, Ahmet (Asian Journal of Medical Sciences, 2014)
Pacing threshold is an important entity which should be tested during pacemaker follow up. Abnormal elevation of pacing threshold would end up with early exhaustion of pacemaker battery. In this report, we described a patient with an unusual cause for threshold elevation. Learning objective: Pacemaker follow-up has its own routines. Telecardiogram is one of them, however it is mostly underrated nowadays. Our objective is to teach value of this quick and inexpensive test for pacemaker patients. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10801 Asian Journal of Medical Sciences Vol.6(1) 2015 106-107